2013
DOI: 10.1038/bjc.2013.562
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-100/99a, deregulated in acute lymphoblastic leukaemia, suppress proliferation and promote apoptosis by regulating the FKBP51 and IGF1R/mTOR signalling pathways

Abstract: Background:MicroRNAs alter multiple cell processes and thus influence tumour carcinogenesis and progression. MiR-100 and miR-99a have been reported to be aberrantly expressed in acute leukaemia. In this study, we focused on their functions in acute lymphoblastic leukaemia (ALL) and the molecular networks in which they are involved.Methods:MiR-100 and miR-99a expression levels were measured in acute leukaemia patients by qRT–PCR. Kaplan−Meier analysis and log-rank tests were used to calculate the survival rate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 52 publications
5
96
1
1
Order By: Relevance
“…Previously, Zheng and his colleague reported that miR-100 was up-regulated in childhood AML and overexpression of miR-100 inhibited the differentiation of granulocyte and monocyte cells and promoted cell survival [94]. On the contrary, they found that miR-100 was down-regulated in childhood ALL and ectopic expression of miR-100 inhibited cell proliferation and enhanced dexamethasone-induced cell apoptosis [80]. Also, Leite's study showed that the expression of miR-100 was reduced during the transition from high grade localized prostate cancer to metastasis [68].…”
Section: Table 1 Dysregulation Of Mir-100 In Different Human Cancersmentioning
confidence: 99%
“…Previously, Zheng and his colleague reported that miR-100 was up-regulated in childhood AML and overexpression of miR-100 inhibited the differentiation of granulocyte and monocyte cells and promoted cell survival [94]. On the contrary, they found that miR-100 was down-regulated in childhood ALL and ectopic expression of miR-100 inhibited cell proliferation and enhanced dexamethasone-induced cell apoptosis [80]. Also, Leite's study showed that the expression of miR-100 was reduced during the transition from high grade localized prostate cancer to metastasis [68].…”
Section: Table 1 Dysregulation Of Mir-100 In Different Human Cancersmentioning
confidence: 99%
“…Interestingly, the most highly expressed miRNA, lvamiR-100, exhibited a particularly high expression level. lva-miR-100 belongs to the miR-99 family, and it has been demonstrated that miR-99 family members regulate cell proliferation, cell migration, and AKT/m TOR signaling (Jin et al, 2013;Li et al, 2013). Considering the particularly high expression of lva-miR-100 in L. vannamei, we suggest that miR-99 family members may have important biological functions in shrimp.…”
Section: Discussionmentioning
confidence: 83%
“…MiR-99a is downregulated in several cancer cell lines and solid tumors including acute lymphoblastic leukemia, 34 hepatocellular carcinoma, 33 prostate cancer, 35 endometrioid endometrial cancer, 32 and lung cancer, 12 but the mechanisms responsible for its downregulation in tumors are still unknown. By overexpression or inhibition, researchers found that miR-99a could suppress cell proliferation, 35 induce G 1 -phase cell cycle arrest, 36 and promote apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…By overexpression or inhibition, researchers found that miR-99a could suppress cell proliferation, 35 induce G 1 -phase cell cycle arrest, 36 and promote apoptosis. 34 The biological targets of miR-99a have been partially identified as FGFR3, 37 FKBP51, and IGF1R/mTOR signaling pathways. 34,38 However, little is known about the upstream of miR-99a or what can regulate miR-99a expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation